The impact of climate change on communal and small-scale livestock farming practices in the Knersvlakte – exploring adaptation strategies - Farmer, Jacklyn (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil)--Stellenbosch University, 2022.